Optimal Options for Diagnosing the Temporomandibular Joint Irin Pathological Occlusion - Aliev Navruz Khasanovich (American Journal of Biology and Natural Sciences, 2024)
The article presents the results of studying the features of the biomechanics of the lower jaw in patients suffering from pain syndrome of dysfunction of the temporomandibular joint. The improvement of the efficiency of diagnostics and differentiation of the non-articular nature of the pathology of patients with BSD TMJ is presented.